The partner of inscuteable/discs-large complex is required to establish planar polarity during asymmetric cell division in Drosophila. - Bellaiche, Y.; Radovic, A.; Woods, D.F.; Hough, C.D.; Parmentier, M.; O'Kane, C.J.; Bryant, P.J.; Schweisguth, F. (Cell, 2001)
Frizzled (Fz) signaling regulates cell polarity in both vertebrates and invertebrates. In Drosophila, Fz orients the asymmetric division of the sensory organ precursor cell (pI) along the antero-posterior axis of the notum. Planar polarization involves a remodeling of the apical-basal polarity of the pI cell. The Discs-large (Dlg) and Partner of Inscuteable (Pins) proteins accumulate at the anterior cortex, while Bazooka (Baz) relocalizes to the posterior cortex. Dlg interacts directly with Pins and regulates the localization of Pins and Baz. Pins acts with Fz to localize Baz posteriorly, but Baz is not required to localize Pins anteriorly. Finally, Baz and the Dlg/Pins complex are required for the asymmetric localization of Numb. Thus, the Dlg/Pins complex responds to Fz signaling to establish planar asymmetry in the pI cell.